2017
DOI: 10.1177/1553350617708725
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Telementoring in Surgery Compared With On-site Mentoring: A Systematic Review

Abstract: Studies reported that telementoring is associated with similar complication rates and operative times compared with on-site mentoring. However, the level of evidence to support the effectiveness of telementoring as a training tool is limited. There is a need for studies that provide evidence for the equivalence of the effectiveness of telementoring as an educational intervention in comparison with on-site mentoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 37 publications
(40 reference statements)
0
47
0
1
Order By: Relevance
“…Although it cannot replace formal learning opportunities, mentoring can help individuals pinpoint specific topics for further study amongst the vast reams of information or to refine clinical skills through interaction with more experienced practitioners, either in person or through virtual networks. 13 Mentorship has been incorporated into novel quality improvement initiatives, while a combination of structured and informal mentorship opportunities within interprofessional teams has the potential to improve coordination of care, the patient experience, and clinical outcomes. 14,15…”
Section: Mentorship Across Missionsmentioning
confidence: 99%
“…Although it cannot replace formal learning opportunities, mentoring can help individuals pinpoint specific topics for further study amongst the vast reams of information or to refine clinical skills through interaction with more experienced practitioners, either in person or through virtual networks. 13 Mentorship has been incorporated into novel quality improvement initiatives, while a combination of structured and informal mentorship opportunities within interprofessional teams has the potential to improve coordination of care, the patient experience, and clinical outcomes. 14,15…”
Section: Mentorship Across Missionsmentioning
confidence: 99%
“…The previous review of this topic compared telementoring against on-site mentoring. 5 This identified that across the included studies there is no significant difference in outcomes, either clinically or educationally, for those trainees who receive telementoring or on-site mentoring. The results of this systematic review are similar, showing that 58% of included studies found no significant difference between outcomes, while 9% found telementoring to be superior.…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous studies have demonstrated that telementoring can be used effectively and reliably in a variety of settings. 5 The studies describing these have a large amount of heterogeneity in the technology used, as well as setting, and outcomes described.…”
Section: Introductionmentioning
confidence: 99%
“…Andersen et al reported that a similar set-up (STAR: System for Telementoring with Augmented Reality) decreases operator focus shifts and improves accuracy when performing port placement and abdominal incisions on a surgical simulator 23. Telementoring of trained surgeons learning new procedures appears to yield similar complication rates and surgical duration compared with on-site mentoring 24. This may not be applicable to operators with more rudimentary surgical skills.…”
Section: Discussionmentioning
confidence: 99%